Inflammatory biomarkers and cardiac injury in COVID-19 patients - Mumtaz, Ayesha; Rehman, Erum; Rahaman, Mohammad Anisur; Rehman, Shazia (Frontiers in Public Health, 2022)
Cardiac injury has received considerable attention due to the higher risk of morbidity and mortality associated with coronavirus disease. However, in a developing country, there is a scarcity of data on cardiac injury in COVID-19 patients related to inflammatory biomarkers. Therefore, the present research retrospectively analyzes data from three territorial hospitals in Pakistan's Punjab province to investigate the potential impact of cardiac injury on the mortality and severity of COVID-19 infected patients. We evaluated 2,051 patients between January 16 and April 18, 2022, with confirmed COVID-19. The majority of the participants were identified as male (64%) with a median age of 65 years. Also, fever, fatigue, and dyspnea were reported as common symptoms. An aggregate of 623 patients (30.38%) had a cardiac injury, and when these patients are compared to those without cardiac injury, the participants were significantly older and had more comorbidities with higher leukocyte counts, elevated levels of C-reactive protein, interleukin-6, procalcitonin, myohemoglobin, creatinine kinase–myocardial band, serum creatinine, high-sensitivity troponin-I, N-terminal pro-B-type natriuretic peptide had a significant amount of multiple ground-glass opacity and bilateral pulmonary infiltration in radiographic results. Participants with heart injury required more noninvasive or invasive mechanical respiration than those who did not have a cardiac injury. Individuals with cardiac injury had higher rates of sepsis, acute respiratory distress syndrome (ARDS), d-dimer concentration, and respiratory failure than those without cardiac injury. Patients who had had a cardiac injury died at a higher rate than those who had not suffered cardiac damage. In the multivariable logistic regression analysis, participants with cardiac injury showed greater odds of COVID-19 mortality and were found associated with older age (OR=1.99, 95% CI=0.04-3.19), elevated cardiac troponin I (OR=18.64, 95% CI=13.16-23.01), the complication of sepsis (OR=10.39, 95% CI=7.41-13.39) and ARDS (OR=6.65, 95% CI=4.04-8.91). Cardiac injury is a frequent complication among patients with coronavirus-induced infection in Punjab, Pakistan, and it is significantly linked to a greater risk of in-hospital mortality.